Sivil toplum kuruluşlarında öyküleme - Seyfi, Murat (My University, 2015)
Küreselleşme ve iletişim teknolojilerindeki gelişmeler ile birlikte artık insanlar mesaj bombardımanı altında yaşamak zorunda kalmıştır. Toplumsal yaşam içerisinde her geçen gün önemi artan ve yeni işlevler kazanan sivil toplum örgütleri ciddi iletişim stratejileri geliştirmek ve profesyonel halkla ilişkiler çalışmaları yapmak zorunda kalmaktadır. Bunun içinde yeni iletişim araçları keşfederek hedef kitle üzerinde davranış değişikliği yaratacak ve belleklerde daha fazla kalmalarını sağlayacak iletişim faaliyetleri yürütmek zorundalar. Bunun için de toplumsal kodları ve belleği oluşturan hikayeler kilit rol oynayabilir. Bu çalışmanın amacı sivil toplum kuruluşlarının halkla ilişkiler çalışmalarında öykülemeyi kullanıp kullanmadığını araştırmak, kurum içi iletişimde yöneticiler tarafından konunun ne oranda desteklendiğini ortaya koymak, öyküleme yaratma sürecinde sivil toplum kuruluşlarının nelere ihtiyacı olduğunu belirlemek ve bu kapsamda bir halkla ilişkiler modeli geliştirmektir. Bu kapsamda çalışmanın literatür bölümünde Sivil Toplum Kuruluşu, Anlatı, Kültür, Öyküleme kavramları derinlemesine incelenerek çalışmanın alt yapısı oluşturulmuştur. Çalışmanın araştırma kısmında ise araştırma modeli tanımlanmış ve niteliksel ölçme aracı olarak görüşme ve içerik analizi yöntemleri açıklanmıştır. Araştırma kapsamında elde edilen verilerin analizi ve yorumlanması sonucunda sivil toplum kuruluşlarının öykülemeyi bir halkla ilişkiler aracı olarak kullanması için bir model önerisinde bulunulmuştur. leme, Anlatı, Halkla İlişkiler, Sivil Toplum Kuruluşu.

Due to globalisation and advancements in communication technologies, people find themselves bombarded with messages. Non-governmental organizations (NGOs), which have been increasingly significant and have begun to have new functions in social life day by day, have to develop sound communication technologies and conduct professional public relations. For this reason, they have to conduct communication efforts which will be able to lead to changes in the behavioural patterns of their audience and which will remain longer in their minds through discovering new communication means. In this respect, stories which shape the social codes and collective memory may be the key to achieve this purpose. This study aims to examine the process in which stories turn into a communication means for non-governmental organizations. During data collection, a qualitative research model has been used; qualitative assessment means has been developed; and data have been collected through in-depth interviews with those non-governmental organizations in 10 countries which use stories in their public relations efforts. The purposes of this study are to determine whether non-governmental organizations use storytelling in their public relations studies; to reveal to what extent managers support the use of it in communication within the institution; to determine the basic needs of non-governmental organizations during the process of developing storytelling; and to develop a public relations model within this scope. Within this context, concepts such as Non-Governmental Organization, Narrative, Culture and Storytelling are examined in the literature section to create the infrastructure of the study. In the research section, the research model used is described and interview and content analysis are clarified as qualitative assessment instruments. As a consequence of the analysis on and interpretation of the data obtained, non-governmental organizations are recommended to use storytelling as a public relations instrument. Key Words: Storytelling, Narration, Public Relation, Non-Governmental Organization.
Keywords: Halkla ilişkiler; Sivil Toplum Kuruluşları